METODE PERHITUNGAN BESARNYA IURAN PEMERINTAH PADA JAMINAN KESEHATAN SEMESTA DI INDONESIA - , HARTATI; , Dr. Adhitya Ronnie Effendie, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
To provide a comprehensive social security, Indonesia to develop and establish Undang-Undang nomor 40 tahun 2004 about SJSN who hold health insurance which aims to ensure that participants receive health care benefits and protection to meet the basic health needs. In this case, health insurance financed through revenue contributions and dues. This assumes health insurance contribution rate determined by the amount of 5% of salary and then calculate the amount of dues to be paid by the Government. Analysis tools are needed to organize the financing of health insurance and benefits available is a method of calculation. Calculation Method on the healthcare system has four main modules, including: demographic and economic module, Module revenue, expenditure and Module Module outcomes, then produced 12 major mathematical equations on the healthcare system (Cichon, 1999). The authors projected population as the initial data before the Government Contribution Calculation Method on Health Insurance in Indonesia.